Instructions for External Focus of Attention Improved Taekwondo Kicking Performance Only Among Less Skilled Youth. Issue 3 (June 2022) - Siltanen, Simo; Bottas, Reijo
External focus of attention (EFA) studies among children have yielded more equivocal results than have those among adults. Some investigators have found an internal focus of attention (IFA) advantage in children and have explained their results by children's generally lower skill levels, compared to adults. According to the constrained action hypothesis, children's lower skill levels are not yet associated with over-learned automatic movement patterns, so their motor performance is not disrupted by IFA instructions. In this study, our objective was to examine a possible interaction effect between children's skill levels and their exposure to either IFA or EFA instructions on motor performance. Our participants were 40 10–15-year-old taekwondo competitors of higher and lower skill levels (based on both the participant's experience and their test performance) who engaged in a taekwondo kicking movement before and after either IFA or EFA instructions. We found improved kicking performance with EFA versus IFA instructions only among less versus more skilled participants.